COMPARATIVE STUDIES OF SOLVATOCHROMISM BEHAVIOUR OF COPPER(I1) AND NICKEL(I1) SCHIFF BASE COMPLEXES (Journal of Sciences, Islamic Republic of Iran)
A series of Schiff Bases of Ni(II) and Cu(II) using acetylacetone (acac), salicylaldehyde (sal), ethylenediamine (en), and o-phenylendiarnine (dabe) were prepared and characterized. The electronic spectra of some copper chelates in various organic solvents depend strongly on the solvent used and the d-d band of Cu(II) shifts to red with the increase of the Donor Number (DN) of solvent. The color changes from blue to green are observed. The mechanism for solvatochromism is discussed in terms of conformational changes and solvent coordination. Among the nickel complexes, Ni (saloph) is brownish red in chloroform and green in pyridine, probably due to the coordination of two pyridine molecules